Association of systemic inflammation with epicardial fat and coronary artery calcification - Gauss, Soeren; Klinghammer, Lutz; Steinhoff, Alina; Raaz-Schrauder, Dorette; Achenbach, Stephan; Garlichs, Christoph D.; Marwan, Mohamed (Inflammation Research, 2015)
Increased epicardial fat volume (EFV) has been shown to be associated with coronary atherosclerosis. While it is postulated to be an independent risk factor, a possible mechanism is local or systemic inflammation. We analyzed the relationship between coronary atherosclerosis, quantified by coronary calcium in CT, epicardial fat volume and systemic inflammation.Using non-enhanced dual-source CT, we quantified epicardial fat volume (EFV) and coronary artery calcium (CAC) in 391 patients who underwent coronary computed tomography for suspected coronary artery disease. In addition to traditional risk factors, serum markers of systemic inflammation were measured (IL-1?, IL-2, IL-4, IL-6, IL-7, IL-8, IL-10,IL-12, IL-13, IL-15, IL-17, IFN-?, TNF-?, hs-CRP, GM-CS, G-CSF, MCP-1, MIP-1, Eotaxin and IP-10). In 94 patients follow-up data were obtained after 1.9 ± 0.5 years.The 391 patients had a mean age of 60 ± 10 years, and 69 % were males. Mean EFV was 116 ± 50 mL. Median CAC was 12 (IQR 0; 152). CAC and EFV showed a significant correlation (? = 0.37; P < 0.001). EFV and CAC were significantly correlated with the traditional risk factors like age, male gender, diabetes, smoking and hypertension. With regard to biomarkers, CAC was significantly associated (negatively) to G-CSF and IL-13. EFV (median binned) was significantly associated (positively) with IP-10 (P = 0.002) and MCP-1 (? = 0.037). In follow-up, EFV showed a mean annualized progression of 6 mL (IQR 3; 9) (P < 0.001); CAC progressed by a mean of six Agatston Units (IQR 0; 30). The progression of CAC was significantly correlated with the extent of EFV (P < 0.001) while there was no significant correlation between progression of EFV or CAC with systemic inflammation markers.Epicardial fat volume and the baseline extent as well as progression of coronary atherosclerosis-measured by the calcium score-are significantly correlated. While both baseline EFV and CAC displayed significant correlations with systemic inflammation markers, biomarkers were not predictive of the progression of CAC or EFV.
EVALuna2:12060